2003
DOI: 10.1002/j.2334-5837.2003.tb02633.x
|View full text |Cite
|
Sign up to set email alerts
|

4.3.3 An Architecture for an Intelligent Requirements Elicitation and Assessment Assistant

Abstract: Requirements engineering is crucial to the success of the system engineering process. Unfortunately, while current generation tools provide good support to requirements capture, they offer only modest assistance for cognitive tasks such as requirements assessment. This paper opens by introducing the attributes needed to define a requirement and the qualities of good requirements and requirements sets. An argument is then presented for the inclusion of artificial intelligence to perform requirements analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Educated humans are innately able to convey complex concepts through natural language but it remains a challenging medium for computer science because words and phrases can be ambiguous and meaning is notoriously difficult to convey concisely in the absence of contextual information and real-world knowledge. Our philosophy to ease this significant problem is to constrain requirements language use via what is known as a "contextfree" grammar (Scott and Cook, 2003).…”
Section: Tool Philosophymentioning
confidence: 99%
See 4 more Smart Citations
“…Educated humans are innately able to convey complex concepts through natural language but it remains a challenging medium for computer science because words and phrases can be ambiguous and meaning is notoriously difficult to convey concisely in the absence of contextual information and real-world knowledge. Our philosophy to ease this significant problem is to constrain requirements language use via what is known as a "contextfree" grammar (Scott and Cook, 2003).…”
Section: Tool Philosophymentioning
confidence: 99%
“…Several strategies have been previously pursued to perform computer-aided requirements assessment. Scott and Cook (2003) reviewed available techniques and identified that Case-Based Reasoning (CBR), while untried in this problem domain, showed the most promise. The reason for selecting CBR is that it mimics the pattern matching process that human requirements engineers employ when assessing requirements (Cook, 1991: p45).…”
Section: Tool Philosophymentioning
confidence: 99%
See 3 more Smart Citations